2018
DOI: 10.1620/tjem.244.113
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Gut Microbiota Profiles between Autoimmune Pancreatitis and Chronic Pancreatitis

Abstract: Host-derived factors alter gut microenvironment, and changes in gut microbiota also affect biological functions of host. Alterations of gut microbiota have been reported in a wide variety of diseases, but the whole picture of alterations in pancreatic diseases remains to be clarified. In particular, the gut microbiota may be affected by malnutrition or impaired exocrine pancreas function that is associated with pancreatic diseases. We here conducted comprehensive analysis of gut microbiota in patients with typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 33 publications
3
24
0
2
Order By: Relevance
“…Enterococcus abundance increased and Bifidobacterium abundance decreased in the patients with SAP. Hamada et al [8] conducted a comprehensive analysis and comparison of gut microbiota between patients with type 1 autoimmune pancreatitis and chronic pancreatitis, and found that Bacteroides ovatus, Streptococcus australis , Streptococcus gordonii , Clostridium lactatifermentans , and Clostridium lavalense were more abundant in chronic pancreatitis patients. However, the effect of anti-inflammation treatment on gut microbiota in SAP patients remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococcus abundance increased and Bifidobacterium abundance decreased in the patients with SAP. Hamada et al [8] conducted a comprehensive analysis and comparison of gut microbiota between patients with type 1 autoimmune pancreatitis and chronic pancreatitis, and found that Bacteroides ovatus, Streptococcus australis , Streptococcus gordonii , Clostridium lactatifermentans , and Clostridium lavalense were more abundant in chronic pancreatitis patients. However, the effect of anti-inflammation treatment on gut microbiota in SAP patients remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that intestinal microbiota structure was changed in SAP rats with decreased abundance of Saccharibacteria and Tenericutes at the phyla level [7]. Hamada et al [8] conducted comprehensive analysis of gut microbiota between patients with type 1 autoimmune pancreatitis and those with chronic pancreatitis, and found that the proportions of Bacteroides , Streptococcus , and Clostridium species were higher in patients with chronic pancreatitis. Using pancreatic enzyme replacement therapy, Nishiyama et al [9] demonstrated that the abundance of key beneficial bacterium in the intestinal tract, including Akkermansia muciniphila and Lactobacillus reuteri , was increased in chronic pancreatitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…These should be considered as potential therapeutic targets, administering supplementation with bile acids, prebiotics, probiotics, or other drugs to protect and strengthen the intestinal barrier [ 24 ]. In this regard, Hamada et al (2018) addressed the relationship of certain strains of intestinal microbiota with a worsening of malabsorption symptoms [ 42 ]. In addition, experimental rat studies have drawn attention to the intestinal microbiota as a possible therapeutic target [ 43 , 44 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Mice lacking acinar Ca 2+ channel, Orai 1, exhibit intestinal bacterial outgrowth and dysbiosis, which ultimately lead to inflammation and death. Hamada et al [28] have conducted a comprehensive analysis of gut microbiota in patients with type 1 AIP by next generation DNA sequencing (NGS). They have found that gut microbiota profile in AIP was different from that in chronic pancreatitis (CP) in that the proportions of Bacteroides, Streptococcus and Clostridium species were lower in patients with AIP.…”
Section: Intestinal Dysbiosis-mediated Aipmentioning
confidence: 99%
“…(1) Genetic loci KLF7, FRMD4B, LOC101928923, MPPED2 in Japanese AIP associated with lacrimal/salivary gland lesions [14] Decreased MST 1 of regulatory T in Japanese AIP with extra-pancreatic lesions [17] FGFBP2 (fibroblast growth factor binding protein type 2): single base deletion in IgG4-RD [19] (2) Persistent exposure of intestinal commensal flora antigen in mouse AIP model Avirulent E. coli (as PAMP activator) induces anti-CA II, anti-LF and ANA in mouse AIP with salivary gland involvement [20] Commensal E. coli-derived membrane protein flagellin (FliC) induces AIP-like inflammation in mouse model [21] Intestinal microflora can activate TLRs and NLRs on basophils to promote Th2 skewing and IgG4 production in the presence of BAFF [22][23][24][25][26] (3) Intestinal dysbiosis-mediated AIP development via pDC activation Decrease in gut Bacteroides, Streptococcus and Clostridium species in patients with AIP, compared to chronic pancreatitis [28] Activation of pDC by innate immune responses against intestinal dysbiosis in experimental mouse AIP [29] BAFF-B cell-activating factor of TNF family; pDC-plasmacytoid dendritic cell; CA-carbonic anhydrase; LF-lactoferrin; ANA-antinuclear antibodies.…”
Section: Intestinal Dysbiosis-mediated Aipmentioning
confidence: 99%